2019
DOI: 10.1101/705244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal single cell transcriptomics reveals Krt8+ alveolar epithelial progenitors in lung regeneration

Abstract: Lung disease is a major health burden accounting for one in six deaths globally 1 . The lung's large surface area is exposed to a great variety of environmental and microbial insults causing injuries to its epithelium that require a regenerative response mediated by tissue-resident stem and progenitor Lung injury activates quiescent stem and progenitor cells to regenerate alveolar structures. The sequence and coordination of transcriptional programs during this process has largely remained elusive. Using singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 84 publications
(105 reference statements)
4
44
1
Order By: Relevance
“…Subclusters AT2-1 and AT2-2 represented typical alveolar type II cells (figure 7a-c and supplementary figure S7). Subcluster AT2-3 contained cells from asbestos-and TiO 2 -treated animals, and was characterised by the expression of Krt8, Krt18, Ndnf and Lgals3 and matched recently described KRT8 + epithelial cells in the distal lung parenchyma (supplementary figure S7) [37]. Finally, cluster AT2-4 was comprised of cells found after asbestos exposure and expressed several genes linked to pulmonary fibrosis, including Retnla (RELMα), Il33 and Chia1 (supplementary figure S7d and supplementary table S7).…”
Section: Resultssupporting
confidence: 61%
“…Subclusters AT2-1 and AT2-2 represented typical alveolar type II cells (figure 7a-c and supplementary figure S7). Subcluster AT2-3 contained cells from asbestos-and TiO 2 -treated animals, and was characterised by the expression of Krt8, Krt18, Ndnf and Lgals3 and matched recently described KRT8 + epithelial cells in the distal lung parenchyma (supplementary figure S7) [37]. Finally, cluster AT2-4 was comprised of cells found after asbestos exposure and expressed several genes linked to pulmonary fibrosis, including Retnla (RELMα), Il33 and Chia1 (supplementary figure S7d and supplementary table S7).…”
Section: Resultssupporting
confidence: 61%
“…3C). Another group of recent studies have also identified an intermediate cell-state between AEC2 to AEC1 differentiation that is marked by elevated expression of KRT8 and increased TGFb1 signaling, which persists in IPF lungs (Jiang et al, 2020;Kobayashi et al, 2019;Strunz et al, 2019). Interestingly, we find similar features in ABIs, suggesting that this intermediate state may not be unique only during AEC2-to-AEC1 transdifferentiation but also during AEC2-to-Basal transdifferentiation and that upregulation of KRT8 and TGFb1 signaling may represent signaling events contributing to metaplastic hAEC2 differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of gene expression along the hAEC2 transdifferentiation trajectory shows that well-established AEC2 marker, LAMP3, and novel hAEC2 marker, HHIP, are quickly lost first as mature hAEC2s transition into ABIs. The emergence of early basal marker, KRT17, and intermediate marker, KRT8 (Jiang et al, 2020;Kobayashi et al, 2019;Strunz et al, 2019), concurrent with the persistence of AEC2 markers SFTPC, ABCA3, and NAPSA, marks the ABI population most prominently seen in early culture at D7 ( Fig. S1E, S2A).…”
Section: Primary Adult Human Lung Mesenchyme Drives Human Aec2 Transdmentioning
confidence: 97%
“…For example, SCG was used for the description of the parenchymal cell composition (Madissoon et al, 2020;Travaglini et al, 2019;Vieira Braga et al, 2019), the identification of novel cell types such as pulmonary ionocytes (Montoro et al, 2018;Plasschaert et al, 2018), the identification of ectopic and aberrant lung resident cell populations in idiopathic pulmonary fibrosis (Adams et al, 2019;Morse et al, 2019;Reyfman et al, 2019) or the investigation of the cellular contribution in lung cancer (Lambrechts et al, 2018;Lavin et al, 2017;Song et al, 2019;Zilionis et al, 2019). These studies in humans have been accompanied by SCG studies describing the cellular compositions in murine lung under homeostatic as well as stress conditions (Angelidis et al, 2019;Aran et al, 2019a;McQuattie-Pimentel et al, 2019;Schyns et al, 2019;Strunz et al, 2019), and during development (Cohen et al, 2018;Guo et al, 2019). Together, these studies illustrate the enormous breadth of SCG technologies to describe the cellular composition of the lung and identify deviations from homeostasis in diseased organ tissues.…”
Section: Introductionmentioning
confidence: 99%